2014
DOI: 10.1192/bjp.bp.113.137414
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance cognitive stimulation therapy for dementia: single-blind, multicentre, pragmatic randomised controlled trial

Abstract: Continuing CST improves quality of life; and improves cognition for those taking AChEIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 35 publications
7
110
2
3
Order By: Relevance
“…Research with other psychosocial interventions indicates sustainability of effects is rare without further maintenance sessions (Orrell et al, 2014). Consequently, regular, and good quality activities should be a core component of care.…”
Section: Discussionmentioning
confidence: 99%
“…Research with other psychosocial interventions indicates sustainability of effects is rare without further maintenance sessions (Orrell et al, 2014). Consequently, regular, and good quality activities should be a core component of care.…”
Section: Discussionmentioning
confidence: 99%
“…Correct 'definite' judgement 22 (19) 4 (3) 26 (10) Correct 'more likely' judgement 17 (15) 17 (12) 34 (13) Equally likely to be in iCST or TAU 65 (57) 80 (57) 145 (57) Incorrect 'more likely' judgement 10 (9) 31 (22) 41 (16) Incorrect 'definite' judgement 0 9 (6) 9 (4) …”
Section: Demographic Informationmentioning
confidence: 99%
“…The first part of the session focused on describing the programme, familiarising carers with the iCST materials and explaining key principles of the intervention. A clip of a DVD developed in the recent maintenance group CST trial 19 was shown in order to demonstrate principles and examples of activities. The second part of the session focused on practising an iCST session with support from the researcher.…”
Section: Training and Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…La estimulación cognitiva se basa en la evidencia empírica que indica que los individuos con demencia conservan cierta capacidad de aprendizaje (Orrell et al, 2014). Por ejemplo, las personas con Alzheimer pueden modificar su conducta en respuesta a contingencias ambientales, siendo capaces de aprender o re-aprender conocimientos y rutinas procedimentales.…”
Section: Principios De Las Terapias No Farmacológicasunclassified